1995
DOI: 10.1203/00006450-199506000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Episodes of Umbilical Cord Occlusion in Fetal Sheep Lead to Preferential Damage to the Striatum and Sensitize the Heart to Further Insults

Abstract: The effect of repeated episodes of asphyxia on the fetal cardiovascular system and CNS was examined. The umbilical cord was occluded for 5 min, four times, at 30-min intervals in 11 chronically instrumented fetal sheep (118-126 d). Fetal electrocorticogram (ECoG), cortical impedance, ECG, heart rate, and blood pressure were continuously recorded for 3 d, after which neuronal loss was determined histologically. Each occlusion resulted in fetal hypoxemia and bradycardia accompanied by increased TIQRS ratio. Prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
2
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 20 publications
(26 reference statements)
6
37
2
1
Order By: Relevance
“…Consistent with previous reports (Mallard et al, 1995b), repeated cord occlusion had profound effects on ECoG activity in the fetal sheep. Although the reduction in amplitude of the electrical signal observed during occlusions was similar between groups, analysis of the frequency components reveled a more pronounced reduction of the spectral edge frequency (SEF) in the hypoxic group.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Consistent with previous reports (Mallard et al, 1995b), repeated cord occlusion had profound effects on ECoG activity in the fetal sheep. Although the reduction in amplitude of the electrical signal observed during occlusions was similar between groups, analysis of the frequency components reveled a more pronounced reduction of the spectral edge frequency (SEF) in the hypoxic group.…”
Section: Discussionsupporting
confidence: 81%
“…These authors concluded that both the degree of hypotension and the increase in the ratio T/ QRS have an impact on the extent of striatal neuronal loss. Although we used the relatively novel fluorescent indicator Fluoro Jade-B to evaluate neuronal death in cortex and striatum, the proportion of dead cells (30%) in our study is in the same range as previously reported (Mallard et al, 1995b).…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations